Любовь не унять: стихи / Валерий Злобин - Злобин Валерий Васильевич (Бон Анца, 2014)
Экземпляры: УКП (20211214) / Инвентарный номер: АП20140729 / Цена: / Сис.шифр: 84(2) / Авт.знак: З-68 / ГРНТИ: 17 / ББК: 84(2=411.2)6-5